A student with mild intellectual disability and two‐step equations. Issue 4 (4th October 2020) - Hord, Casey; DeJarnette, Anna F.; McMillan, Leah A.; Baldrick, Paige
Abstract : The authors of this study conducted an exploratory study of the teaching and learning processes of a tutor and a student with a mild intellectual disability (MID) while working on two‐step equations. The researchers focused on situations in which the participant was likely to struggle with memory and processing as well as the challenges of the mathematics tasks with which he was presented. The student benefitted from his own use of strategically organised work on pencil and paper as well as the teacher's use of gestures and strategically asked questions designed to promote his progress, yet not interfere with his critical thinking. While the student did experience some challenges, this study demonstrated a case in which a student with a MID solved and discussed two‐step equations successfully.